The origin of the high reactivity of triazolinediones (TADs) in Diels-Alder reactions from a theoretical perspective (2020)
We investigate on the origin of the high reactivity of triazolinediones compared to maleimides in Diels-Alder reactions by using a combination of Molecular Orbital Theory and the Activation Strain Model of reactivity. Calculations at M06-2X/6–311++G(d,p)//M06-2X/6-31+G(d) level show that the energy barrier of the cycloaddition between anthracene and triazolinedione is much lower than that for maleimides. The analysis of frontier molecular orbitals (FMO) reveals that for the TAD system there is a much efficient charge transfer as consequence of a more delocalized HOMO over the dienophile fragment at the transition state structure. The Activation Strain Model revealed that the higher reactivity of TAD in the cycloaddition is related to the lower distortion of both fragments to attain the geometry of the transition state. © 2020 Elsevier Ltd